Barn owls - Neuenfeldt, Elizabeth (Bellwether Media, Inc., 2024)
"Relevant images match informative text in this introduction to barn owls. Intended for students in kindergarten through third grade"--
Includes bibliographical references (page 23) and index.
Ages 5-8
Grades 1-2
Keywords: Barn owl -- Juvenile literature; Barn owls